Capturing the Digital Economy a proposed measurement framework and its applications a special supplement to key indicators for Asia and the Pacific 2021. (Key indicators for Asia and the Pacific., 2021)
Amid the growing interest in the digitalization of socioeconomic activities, there is a lack of consensus on an established framework to estimate the digital economy. This report proposes a definition of the core digital economy and an input output analytical framework to measure it. Applying this framework to selected economies and years, it finds that the digital economy and digitally dependent industries contribute a significant portion of gross domestic product. It examines key digital economy phenomena and trends in relation to sectoral links, temporal price changes, jobs, global value chains, the COVID-19 pandemic, and Industry 4.0.